Increase of Serum Zinc Levels in Patients with Vitiligo - Dinar Witasari; Hari Sukanto; Trisniartami Setyaningrum (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Vitiligo is a common acquired depigmentary disease characterized by depigmented patches of the skin, hair, and mucous membranes due to selective destruction of melanocytes. Zinc is one of the trace element that suspected to play an important role in pathogenesis of vitiligo. Previous research showed a controversial result in zinc level of vitiligo. Purpose: To compare serum zinc between vitiligo and control in Dermatology and Venereology Outpatient Clinic in Dr. Soetomo General Hospital Surabaya. Methods: Analitic observational case control research was conducted, with 19 vitiligo patients in Dermatology and Venereology Outpatient Clinic Dr. Soetomo hospital and 19 age-sex matched controls (non-vitiligo subjects) that were qualified with inclusion and exclusion criteria. Serum zinc level was measured in both groups using atomic absorbtion spectrophotometer. Results: Mean serum zinc in vitiligo groups were 254.53 µg/dL and 109.53 µg/dL in control groups. This results showed that mean serum zinc in vitiligo group significantly higher compared to control group (p<0,05). There was a statistically significant association between serum zinc level and progressivity of the lesion as patient with active vitiligo lesion showed higher values of serum zinc. Stress is the most common predisposing factors (36%), meanwhile stress can also induce the increasing of serum zinc. Conclusion: Serum zinc in vitiligo patient is higher than control and showed correlation with course of the disease. It is required further research to reveal the role of zink in vitiligo and the connection between the degree of stress and serum zinc.